Dragon Puff Corporation a production systems study - Ansaldo, Maria Lalaine; Banlaoi, Jethro L.; Gorospe, Virginia; Herrera, Ma. Cecilia; Otico, Edward; Romanes, Maia. (Diliman, Quezon City College of Engineering, 1993)
A production system study was made on Dragon puff Corporation which manufactures several brands of cigarette through three main process departments, 1) Primary Department, 2) Making Department, and 3) Packing Department. Different tools and techniques were used to identify and analyze the problems in six subsystems: 1) Materials Management, 2) Inventory Control, 3) Quality Control, 4) Maintenance, 5) Scheduling and 6) Human Resource Management. The two root causes of problems were poor implementation of standard procedures and poor policy-making and planning by management. Capacity planning was made based on the ideal capacity of the plant. It emphasized that the existing production system has a low efficiency and poor quality control mechanism which are manifested by frequent breakdown of equipment and substantial wastage in materials, man and machine hours. Total Quality management as a continuous quality improvement approach was recommended to address the root causes of problems. Specific recommendations under the different subsystems were also made. A phase by phase procedure was included as implementation guide for TQM.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Dragon Puff Corporation; Cigarette industry; Production engineering